2017
DOI: 10.1002/prep.201700070
|View full text |Cite
|
Sign up to set email alerts
|

Full‐field Peak Pressure Prediction of Shock Waves from Underwater Explosion of Cylindrical Charges

Abstract: Cylindrical charge is a main form in most application of explosives. By employing numerical calculation and an indirect mapping method, the relation between peak pressures from underwater explosion of cylindrical and spherical charges is investigated, and further a model to predict full‐field peak pressures by the former one is developed and then verified by experiments. Besides, a method to intuitively sketch the corresponding orientational performance is proposed and discussed. The results indicate the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The impulse is close to being spherically symmetric while the EFD exhibits asymmetry about the charge. General trends agree with similar studies conducted in literature [23,37].…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…The impulse is close to being spherically symmetric while the EFD exhibits asymmetry about the charge. General trends agree with similar studies conducted in literature [23,37].…”
Section: Methodssupporting
confidence: 92%
“…The EFD is slightly less for the cylindrical solution. Again, these results are in agreement with general trends observed in literature [23,37]. We conclude that the use of spherical solutions is justified provided that gauges are located on the radial axis (90°in Figure 3) and have shown that the distances from the charge in Table 5 are compatible with this approach.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Usually, if the bubble oscillates at a very close distance near the surface of the structure or free surface, either the bubble motion cycle or the maximum bubble radius will be much affected , the bubble will be rejected at the expansion stage, and be drawn at the collapse stage, and a water jet will form ,which can be explained by the Bjerkness effect [31].While, in most cases of this work, the test distance and water depth was much bigger than the maximum bubble radius (Fig. 7), namely, / > 2 and / > 2, so, the experiment condition can be approximately treated as mid-field or far-field underwater explosion [32]. Mu [33] applied MSC.…”
Section: Input Shock Loadingmentioning
confidence: 72%
“…Xiao et al [24] improved the compressible nonspherical bubble dynamics model and explored the influence of bubble initial conditions in the free field and gravitational field on bubble dynamics. Liu et al [25] used numerical calculations and indirect mapping methods to study the similarities, differences, and relationships between spherical and cylindrical charges in underwater explosions and verified them through experiments. Ming et al [26] used the SPH method to study the shock wave load characteristics near the underwater explosive charge and proposed a SPH-FEM method to study the dynamic nonlinear behavior of ship structures under the action of underwater explosions.…”
Section: Introductionmentioning
confidence: 99%